Simple Menus of Contracts in Cost-Based Procurement and Regulation - Rogerson, William P (American Economic Review, 2003)
This paper develops an extremely simple formulation of the Laffont-Tirole principal agent model of cost-based procurement and regulation which is suitable for applied uses by restricting the principal to using a two item menu where one item is a cost-reimbursement contract and the other item is a fixed price contract.Menus of this form are called fixed-price-cost-reimbursement (FPCR) menus.In the case where the agent's utility is quadratic and the agent's type is distributed uniformly, it is shown that the optimal FPCR menu always captures at least three quarters of the gain that the optimal complex menu achieves.Therefore, at least for the uniform quadratic case, extremely simple menus with low informational requirements perform nearly as well as the fully optimal complex menu.